Comparison of one step glucose tolerance test (75 g GTT) and two step glucose tolerance test (100 g GTT) in screening and diagnosis of gestational diabetes mellitus - N., Saranya; M., Suganthi; Dhinakaran, Shanthi; N., Navina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Studies suggesting that increasing carbohydrate intolerance among patients not meeting the criteria for the diagnosis of GDM by two step OGTT leads to an increased rate of unfavourable maternal and perinatal outcomes. Patients with abnormal GCT results but a normal OGTT are at increased risk, as are those with one abnormal OGTT value rather than the two required for diagnosis by ADA criteria. Single value of one step GTT is enough to diagnose GDM and to improve the maternal and perinatal complications. The objective is to compare the efficacy of one step OGTT with two step OGTT in screening and diagnosis of gestational diabetes mellitus. Methods: Hospital based analytical cross-sectional study which was conducted for 1 year among all pregnant women booked at government medical college, Alappuzha. They were subjected to detect GDM by 2 methods at 24-28 weeks. Results: 2521 pregnant women were subjected for study, among them who were either 75 gm GTT or 50 gm GCT or both positive (332 pregnant women) were analyzed. 232 women (69.88%) were diagnosed as having gestational diabetes mellitus (GDM) by single step 75 gm GTT. Sensitivity of single step GTT was 92.4% and a false negative rate of the same was 7.6%. False negative rate for 50 gm GCT was 35.2%. Conclusions: Present study concluded that this one step procedure is feasible in terms of better detection rates, saving time, limiting cost on repeated visits to health centre and reducing repeated invasive sampling. Single step GTT will be used both as a screening and a diagnostic procedure for detecting GDM.